2007
DOI: 10.1210/jc.2006-0600
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Cardiovascular Response to Growth Hormone Therapy in Adult Patients with Prader-Willi Syndrome

Abstract: In PWS, GH therapy increased cardiac mass devoid of diastolic consequences. The observation of a slight deterioration of right heart function as well as the association between IGF-I and left ventricular function during GH therapy suggest the need for appropriate cardiac and hormonal monitoring in the therapeutic strategy for Prader-Willi syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…Our randomized placebo controlled study (n = 46) found reductions in visceral fat and subcutaneous abdominal fat of nearly 25% and 20%, respectively, as measured by CT subcutaneous thigh fat was reduced by 12%, and thigh muscle volume increased by 6% [17]. Marzullo et al [24] found similar effects on visceral and subcutaneous fat in an openlabeled study (n = 13) and changes in total body composition as measured by DXA has also been reported by Mogul et al (n = 38) [16], and Gondoni et al (n = 12) [14]. Thus, all studies report an increase in lean body mass ranging from 2.2 kg to 3.3 kg and a decrease in total body fat ranging from 2.5% to 6%.…”
Section: Discussionmentioning
confidence: 63%
“…Our randomized placebo controlled study (n = 46) found reductions in visceral fat and subcutaneous abdominal fat of nearly 25% and 20%, respectively, as measured by CT subcutaneous thigh fat was reduced by 12%, and thigh muscle volume increased by 6% [17]. Marzullo et al [24] found similar effects on visceral and subcutaneous fat in an openlabeled study (n = 13) and changes in total body composition as measured by DXA has also been reported by Mogul et al (n = 38) [16], and Gondoni et al (n = 12) [14]. Thus, all studies report an increase in lean body mass ranging from 2.2 kg to 3.3 kg and a decrease in total body fat ranging from 2.5% to 6%.…”
Section: Discussionmentioning
confidence: 63%
“…A small reduction in LDL cholesterol was found. This is a new finding because none of the previous GH intervention studies have reported this (14,15,24). However, despite the fact that PWS patients in most studies are obese, hypercholesterolemia does not seem to be frequent in the PWS group, probably related to the smaller amount of visceral fat.…”
Section: Discussionmentioning
confidence: 75%
“…LVEDD increased significantly after 12 months of GH treatment. Right ventricular ejection fraction measured by radionuclide ventriculography, that was not different from obese controls at the start of GH, decreased significantly over the first 12 months of GH treatment, indicating the possible development of right ventricular dysfunction [24]. In the PWS cohort treated in our institution, 2 children had developed oligosymptomatic cardiac dilatation and decreased cardiac function detected by echocardiography and confirmed by cardiac MRI, while under GH treatment for 5.5 and 2.75 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, in view of reported cardiac deaths unrelated to obesity, in view of our 2 cases of dilative cardiomyopathy after years of GH treatment, and in awareness of reports that some adult PWS patients treated with GH might progress into decreased diastolic function [24], regular echocardiographic assessment including functional parameters may be considered at least for older PWS children and adolescents on GH therapy of longer duration.…”
Section: Discussionmentioning
confidence: 99%